Faham behaviorime dan penjelasan tentang perilaku insan: satu analisis kritikal - Hashim, Rosnani (Institut Pengajian Ilmu-Ilmu Islam (IPI-ABIM), 2000)
This article discusses the origin cum emergence of behaviorism as a mechanics in applying scientific method in education. Albeit the subject matter of behaviorism is focused on mundane matters of human actions, it also deals with introspective psychology. What constitutes behaviorism and what are its inherent flaws? These are the questions that the present writer tries to underscore. Thus, a major part of this paper deals with a critical discussion on behaviorism both from western and Islamic perspectives. What is revealing is that behaviorism as a discipline of study not longer commands advocacy of the majority today.